Functional outcomes of ulnar nerve neurotization by anterior interosseous nerve in high level injury - HH Noaman; Mohammed A Mohamed; Yasser Othman Sorour (Journal of Surgery and Surgical Research - Peertechz Publications, 2021)
Background: The ulnar nerve injury induce sever hand malfunction due to intrinsic muscle paralysis. The ulnar nerve repair in proximal area (high ulnar nerve injury) seldom leads to intrinsic muscle function because of long distance of nerve return. Therefore, the best techniques to restore intrinsic hand function in patient with high ulnar nerve injury is distal nerve transfer to minimize the regeneration time and distance.   Objective: The aim of this study is to describe the surgical results obtained with the transfer of the motor branch of the anterior interosseous nerve destined to the pronator quadrates muscle to the motor division of the ulnar nerve (the deep branch of ulnar nerve). Methods: It is a retrospective study of thirty elderly patients with high ulnar nerve injury underwent a transfer of distal branch of anterior interosseous nerve to deep branch of ulnar nerve, and end to end suture of the ulnar nerve at the site of injury in Sohag microsurgery unit.  Results: The mean postoperative follow-up period was 22 months (range from 12 to 38 months). At the final follow-up, twenty-seven (90%) patients showed good results according to the Highet-Zachary scheme (M3 or M4, S3+, and negative Froment's sign). The other three patient (10%) showed a poor result (M1, S2, positive Froment's sign). Conclusion: This technique of transfer of distal branch of anterior interosseous nerve to deep motor branch of ulnar nerve and primary repair of ulnar nerve at site of injury is effective for motor and sensory recovery of distal ulnar innervated side of the hand.